Nursing Intervention Management to Improve Upper Extremity Muscle Strength in Stroke Patients - Tri Wahyuni Ismoyowati; Sahat Tumpal Salomo; Henry Agus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Aims: Stroke is the leading cause of death, accounting for 15.45% of deaths each year. Stroke is a central nervous system disorder that can lead to paralysis of limbs and muscle weakness. Nursing interventions to improve muscle strength include mirror therapy and Constraint-Induced Movement Therapy (CIMT). This study aims to determine the effects of mirror therapy and CIMT on muscle strength in the extremities of stroke patients. Method: Case report design was used, with pre-and post-tests conducted to evaluate muscle strength in patients. Purposive sampling was employed with inclusion criteria, and the sample consisted of two patients. The intervention involved mirror therapy twice daily, in the morning and evening for 5 days, with each session lasting 30 minutes—two 15-minute sessions with a 5-minute break in between. The CIMT intervention was performed for five days, with each session lasting 30 minutes. Muscle strength was assessed using Manual Muscle Testing (MMT). Results: After the mirror therapy and CIMT interventions, there was an improvement in muscle strength in the upper extremities. Conclusion: Both mirror therapy and CIMT can enhance muscle strength in the extremities of patients with stroke.